2018
DOI: 10.1007/s00289-018-2632-3
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate-based thermoplastic polyurethane elastomers modified by DMPA

Abstract: Thermoplastic polyurethane elastomers (TPUs) containing aliphatic polycarbonate soft segments and hard segments formed by 1,1′-methanediylbis(4-isocyanatocyclohexane) or 1,6-diisocyanatohexane and a combination of two chain extenders, i.e., 2,2′-[sulfanediylbis(benzene-1,4-diyloxy)]diethanol and 3-hydroxy-2-(hydroxymethyl)-2-methylpropanoic acid (DMPA), were synthesized in a onestep catalyzed melt polyaddition process. The obtained colorless, transparent and high-molar-mass materials, which differ in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The use of chain extenders containing sulfur atoms in their structure is the subject of mine and my colleagues’ research. Of the many systems available, we have synthesized derivatives of diphenylmethane [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], diphenylethane [ 48 , 49 , 50 , 51 , 52 ], benzophenone [ 53 , 54 , 55 ], diphenyl ether [ 56 ] and diphenyl sulphide [ 38 , 57 , 58 , 59 , 60 ]. In our previous studies, we have attempted to obtain and investigate the effects of such unconventional chain extenders on the structural, thermal, mechanical and optical properties of novel polyurethane materials.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chain extenders containing sulfur atoms in their structure is the subject of mine and my colleagues’ research. Of the many systems available, we have synthesized derivatives of diphenylmethane [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], diphenylethane [ 48 , 49 , 50 , 51 , 52 ], benzophenone [ 53 , 54 , 55 ], diphenyl ether [ 56 ] and diphenyl sulphide [ 38 , 57 , 58 , 59 , 60 ]. In our previous studies, we have attempted to obtain and investigate the effects of such unconventional chain extenders on the structural, thermal, mechanical and optical properties of novel polyurethane materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a polyblend of epoxidized natural rubber/TPU it was found that rice husk ash particles had stronger interactions with epoxidized natural rubber and provided enhanced mechanical properties to the rubber [49]. TPU elastomers having aliphatic polycarbonate soft segments and hard segments made by 1,1'-methanediylbis(4isocyanato-cyclohexane) or 1,6-diisocyanatohexane and a combination of two chain extenders were synthesized in one-step catalyzed polyaddition [50].…”
Section: Pu Elastomersmentioning
confidence: 99%
“…The material morphology, mechanical properties, and thermodynamic characteristics of these TPU elastomers were fully characterized and indicated differences in cryogenic performance caused by microphase separation. [19][20][21][22] Combined with molecular structure and interchain interaction, the effect of cyclic amine chain extenders on the microphase separation and subsequent cryogenic performances of these TPUs is discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The chain extender definitively influences the cryogenic performance of these TPU elastomers, as expected, and gave rise to better low‐temperature resistance and more robust mechanical properties than the control elastomer TPU‐BD using BDO as the chain extender. The material morphology, mechanical properties, and thermodynamic characteristics of these TPU elastomers were fully characterized and indicated differences in cryogenic performance caused by microphase separation 19–22 . Combined with molecular structure and interchain interaction, the effect of cyclic amine chain extenders on the microphase separation and subsequent cryogenic performances of these TPUs is discussed in detail.…”
Section: Introductionmentioning
confidence: 99%